E-Cigarette Vaping and Periodontium: A Systematic Review - Ameer A. Altabatabaie1 , Ahmed A. Alquzweeni2 , Hussein A. Alnajar3 , Raya Ali Dalol4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Conventional cigarettes have shown severe toxicity on immune cells and wound healing in the periodontium,but little is known about the comparative effects of vaping or electronic cigarettes. If current conventionalcigarette users are to transition to a less detrimental alternative, the evidence must demonstrate if electronicnicotine delivery systems can be deemed safer than conventional options. The intent of this literature is tosummarize the evidences on the effect of E-cigarette on the periodontal health.The main sources of evidence for this report included: a comprehensive report from National Academies ofSciences, Engineering, and Medicine, reviews published in the past 10 years.As a conclusion, further investigation and studies are needed to evidence the effect of new smoking methodson the oral health of newly users and on the shifted persons who was previously tobacco smokers.